The Strategy Head Madrasah Strengthening The Quality Of Education In Madrasah Ibtidaiyah - Chostholani, Akmad; Usman, Fadly; Zamroni, Afif (ZAHRA: Research and Tought Elementary School of Islam Journal, 2021)
This article aims to explain and analyze planning, implementation and evaluation strategies in strengthening the quality of education at Madrasah Ibtidaiyah Tarbiyatul Islamiyah Gresik. This article uses a qualitative research type with a descriptive design. This research takes place at Madrasah Ibtidaiyah Tarbiyatul Islamiyah Gresik. The research was carried out for three months, from February to May 2021. The technique of collecting data was observation, interviews with relevant informants and documentation. The results of this study are how madrasah strategies in strengthening the quality of education in institutions, both in terms of planning, implementation, and evaluation are strongly influenced by the madrasa head as a leader. Because all the strategies and policies used by the head of the madrasa determine the quality of an educational institution that is led. There are several things that the head of Madrasah Tarbiyatul Islmiyah does in strengthening the quality of education, including: 1) Providing examples of direct action with time discipline, 2) Carrying out programmatic and consistent implementation of activities, 3) Always evaluating programs carried out both internal and external evaluations. from outside so as to obtain accountable results.